THE POWER OF THAI DEMONSTRATIONS AGAINST THE ROYAL FAMILY - Saragih, Hendra Maujana; Suhayatmi, Suhayatmi; Zulham , Muhammad (Journal of Social Political Sciences, 2021)
Thailand has a long history of political riots and protests, but the pro-democracy actions that took place for most of 2020 and are continuing today are the biggest actions in Thai history. The wave of actions bearing the 'Three Fingers' symbol began in February 2020 after the Thai Raksa Chart, the most outspoken opposition political party, was suspended by the Constitutional Court. This freeze is considered by democracy activists to increasingly benefit the ruler of the military junta, Prime Minister Prayuth Chan Ocha. There were at least 10 demands made by the demonstrators, among others, urging the ruling government to step down immediately, demanding amendments to the military product constitution which is not pro-people, immediately holding fair and fair elections, and pressing for reform of the monarchy that has ruled Thailand for decades. The demonstrators were worried that Thailand would again be trapped in an absolute monarchy system as it was before 1932, where the king held full power as head of state as well as head of government. In recent months, demonstrators have taken to the streets to resist resistance. Although the pro-democracy activists were responded to, the demonstrators, who were mostly students, students, and youth ranks, fearlessly continued to embrace to pressure the royal family. Actions against the monarchy like those of the country's demonstrators were both courageous and surprising. Why not, since birth in the realm of the body, Thai citizens have been instilled to love and obey the monarchy unconditionally and are instilled to be afraid to do things that are against or just talk about the royal family. However, the anger, disgust of the Thai people towards the feudal behavior of the royal family who are busier with self-interest coupled with the Military Junta ruling regime that is not pro-people makes their patience limit is on the limit.